Probation officer discretion in monitoring and violating supervision conditions - Ruhland, Ebony L. (Probation journal, 2022)
Probation is a sentence served in the community and includes a number of supervision conditions. If the conditions are violated, individuals could receive a sanction, including revocation. Not every violation, however, may receive a consequence. Probation officers have discretion for how they manage individuals on the caseloads. This study used qualitative data from two departments in a MidWest state in the United States, one rural and one urban, to explore officer decision-making in supervision. It is critical to examine these factors due to the high number of individuals revoked from probation each year. The study findings illustrate the factors officers use in monitoring conditions, as well as in violations and revocations.